An efficient algorithm for solving fractional differential equations with boundary conditions - Alkan, Sertan; Yildirim, Kenan; Secer, Aydin (SCIENDO, 2016)
In this paper, a sinc-collocation method is described to determine the approximate solution of fractional order boundary value problem (FBVP). The results obtained are presented as two new theorems. The fractional derivatives are defined in the Caputo sense, which is often used in fractional calculus. In order to demonstrate the efficiency and capacity of the present method, it is applied to some FBVP with variable coefficients. Obtained results are compared to exact solutions as well as Cubic Spline solutions. The comparisons can be used to conclude that sinc-collocation method is powerful and promising method for determining the approximate solutions of FBVPs in different types of scenarios.
Keywords: Fractional differential equations; boundary value problems; sinc-collocation method; Caputo derivative; Physics